ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK DITINJAU DARI KEMANDIRIAN BELAJAR PESERTA DIDIK SMP NEGERI 1 BAGAN SINEMBAH PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL (Math Educa Journal, 2021)
The mathematics problem solving ability has an important role in mathematics learning process.  One of factors influencing mathematics problem solving ability is learning independence.  This research aimed at analyzing student mathematics problem solving ability viewed from learning independence that was focused on linear equation system two variables material.  The methods of collecting the data were test for mathematics problem solving ability, questionnaire for students learning independence, and interview. The findings of this research showed that the student high learning independence category owned the lowest ability in crosscheck the solution.  The student medium learning independence category owned the lowest ability in preparing strategies and crosscheck.  The student low learning independence category owned the lowest ability in preparing strategies, carrying out the strategies and crosscheck.  The implication of this research was expected for teacher to accustom students to crosscheck every problem solving step given to SPLDV questions in learning process.  Teacher was expected to use an approach that is able to increase student learning independence.